Effects of Aerobic Exercise on Physical Condition in Chronic Kidney Disease Patients: Scoping Review - Iftinan Nida Firdaus; Meira Erawati; Wahyu Hidayati (Indonesian Journal of Global Health Research, 2024)
Chronic kidney disease (CKD) can cause changes in physical condition and cause cardiovascular problems to death. The development of CKD can be prevented by doing physical activity, one of which is aerobic exercise. Studies related to the effects of aerobic exercise on physical condition, especially in patients with chronic kidney disease, are still limited, so further studies are needed. The purpose of this study was to determine the effect of aerobic exercise on physical condition in patients with chronic kidney disease. The method used is a scoping review based on the PRISMA flow diagram. Article searches were conducted using electronic databases or internet searches, some databases used as article selection are ScienceDirect, Pubmed, and Springerlink. In conducting the search using the keywords "Aerobic Exercise" and "Chronic Kidney Disease" and "physical condition". Where in the screening or filtering of articles are given the filters "2020-2024", "Free full text" and "research article". The scoping review analysis was carried out using the Arksey and O'Malley theory approach which has been modified by Levac. From 4 databases, 6 articles were analyzed and focused on the effect of aerobic exercise on physical conditions in patients with chronic kidney disease. The results of the analysis showed that aerobic exercise significantly increased the SPPB (Short physical performance battery) value, increased the HRV (heart rate variability) index within the normal range, increased vagal activity leading to sympathovagal balance, improved systolic and diastolic values, increased physical activity levels, and decreased blood glucose and increased hematocrit.The effect of Aerobic exercise on the physical condition of patients is divided into physiological and biochemical effects. The effect of Aerobic exercise on physical conditions physiologically is to improve physical function, functional capacity and activity of the autonomic nervous system of the heart, increase blood flow, reduce risk factors for cardiovascular disease, increase cardiorespiratory capacity and muscle strength of the upper and lower body, and have a more comprehensive range in activities. The effect of Aerobic exercise on physical conditions biochemically is to maintain stable blood levels.